Malaysia one year after: an interview with Tan Sri Syed Hamid Albar - Noh, Abdillah (Taylor & Francis, 2019)
Malaysia experienced the first change of government since its independence in 1957 when the Barisan Nasional (BN) was defeated by the Pakatan Harapan (PH, “Alliance of Hope”) coalition on May 9, 2018. The twist to the plot is that the PH victory was led by Dr Mahathir Bin Mohamad, who previously had served as prime minister for twenty-two years as a member of the BN. At ninety-three years old Mahathir broke his allegiance with the BN and the United Malay National Organisation (UMNO) - the major component party of the BN – to join hands with opposition leaders who were once his arch enemies.